Effect of Tillage and Organic Manures on Soil Moisture and Performance of Rainfed Groundnut (Arachis hypogea L.) - Sanepara, D. P.; Vekariya, P. D.; Vora, V. D.; Gajera, M. S.; Akbari, K. N. (International Journal of Bio-resource and Stress Management, 2015)
A field experiment was conducted during rainy season of 2000 to 2005 on medium black clay soil at Main Dry Farming Research Station, JAU, Targhadia (Rajkot) to find out suitable tillage practice with organic manure for obtaining higher yield of groundnut. Main plot comprised of three tillage practices viz., every year deep ploughing in set row furrows, alternate year deep ploughing in alternate set row furrows and farmer’s practice (opening the set row furrows only) and sub-plot of two organic manures viz., farm yard manure @ 5 t ha-1, farm residues @ 5 t ha-1 and control (no organic manure) were evaluated in split plot design with four replications. Significantly higher pod yield were recorded under alternate year deep ploughing in alternate set row furrows and FYM @ 5 t ha-1 as compared to farmers practice and farm residues @ 5 t ha-1, respectively. The soil moisture content was found non-significant due to tillage practices, while it was recorded significantly higher under application of FYM @ 5 t ha-1 and farm residues @ 5 t ha-1 than control. Similarly, significantly higher soil moisture content was also recorded under the combination of every year deep ploughing in set row furrows and FYM @ 5 t ha-1. Alternate year deep ploughing in alternate set row furrows gave the highest net returns of Rs 13742 ha-1 with the B:C ratio of 1.96. While application of FYM @ 5 t ha-1 gave the highest net returns of Rs. 13888 ha-1 with B:C ratio of 1.89.